Hydrogels for Engineering the Immune System. Issue 3 (1st February 2021) - Li, Xianlei; Shou, Yufeng; Tay, Andy
Abstract : Human immune system has evolved as one of the most powerful defense systems to protect against invading pathogens and mutated cells. However, when persistent immune suppression or activation occurs, it can lead to adverse, chronic physiological effects including cancer and arthritis. Hydrogels are soft materials that can be engineered to modulate immune responses through controlled biomolecule release/adsorption, regeneration of lymphoid tissues, and enhanced antigen presentations. This is achieved by programming hydrogels to exhibit optimal properties such as porosity, biodegradability, and biocompatibility to interface seamlessly with the immune system. Herein, recent innovations and future challenges are described using programmable hydrogels to regenerate the lymphatic system, modulate inflammation, and enhance cancer immunotherapy. Key properties of hydrogels are also highlighted for engineering the immune system and techniques to characterize these properties. Abstract : Hydrogels are soft materials that can be engineered to modulate immune responses through controlled biomolecule release/adsorption, regeneration of lymphoid tissues and enhanced antigen presentations. Herein, recent innovations and future challenges are described using programmable hydrogels to regenerate the lymphatic system, modulate inflammation and enhance cancer immunotherapy.